Replication data for: Correlations between modest weight loss and leptin to adiponectin ratio, insulin and leptin resensitization in a small cohort of Norwegian individuals with obesity. - Isaksen, Victoria Therese; Larsen, Maria Arlén; Goll, Rasmus; Paulssen, Eyvind Jakob; Florholmen, Jon (DataverseNO, 2019)
The present dataset is the basis of the results presented in \"Modest weight loss improves leptin to adiponectin ratio and induces insulin and leptin resensitivization in individuals with obesity.\" (manuscript submitted 2019, December). Please read the accompanying ReadMe file for a further description of variables. Abstract: Background: Identifying patients at the highest risk of adverse consequences of obesity is of great importance in order to better monitor the effects of treatment. This study aims to investigate whether dysregulated adipokines and postprandial triglycerides (TG) improve with modest weight loss. Methods: Individuals with obesity were recruited by posters, among patients at the University Hospital of North Norway and the Stamina Health weight loss program. We calculated the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), leptin to adiponectin (L:A) ratio, indirect leptin sensitivity (REE:leptin ratio), postprandial TG clearance at 6 h and TG response from samples collected at visits before and after weight loss. The weight loss goal was ≥5% of initial total weight. Results: Twenty-eight participants attended both assessments, of which 13 lost ≥5% body weight. Of these, five lost ≥10% body weight. HOMA-IR (-23.1%), REE:leptin ratio (+80.1%) and L:A ratio (-45.7%) significantly improved with a weight loss ≥5%, whereas there was no improvement of postprandial TG response or clearance. Participants with ≥5% weight loss improved their L:A ratio over cut-off values ≥1.88 and ≥2.2 significantly, and participants with ≥10% weight loss improved their L:A ratio over the cut-off value ≥3.65 significantly. Participants with ≥10% weight loss also improved their HOMA-IR over cut-off value ≥2.3 significantly. Conclusion: Metabolic dysregulation measured by the surrogate biomarkers HOMA-IR, REE:leptin ratio and L:A ratio, but not postprandial TG, improve with a modest weight loss of ≥ 5%. Further improvements in these biomarkers are seen in weight loss of ≥10%. To measure postprandial TG response (TGR) and TG clearance, we performed an Oral Fat Tolerance Test (OFTT). Participants had their regular diet and abstained from vigorous exercise three days before the test, and showed up at 08:00 am after a 12 h overnight fast. Fasting blood samples were drawn, and a meal of sour cream porridge was served, containing 1 g of fat per kg of body weight (28). The participants ingested the meal within 30 minutes, and blood samples were drawn from the antecubital vein in a seated position at baseline and 2, 4, 6 and 8 h postprandially. We calculated TG clearance in per cent of the peak value at 6 and 8 h, in addition to the TGR, defined as the average of the two highest postprandial TG concentrations, minus the baseline concentration. The formula for calculating TG clearances (28) at time X was as follows: Clearance Xh =100×(1- ([TG]X -[TG]0h)/([TG]max -[TG]0h )) We performed a 2 h Oral Glucose Tolerance Test (OGTT) on a separate day. Preparations for the OGTT were the same as for the OFTT and was conducted by oral intake of 75 g glucose, dissolved in water. We collected blood samples in both the fasting state and 30, 60, 90 and 120 minutes after glucose intake, in which serum glucose and serum insulin were measured using ELISA kits (DRG Insulin Elisa kit, DRG Instruments GmbH, Germany). We determined insulin sensitivity by calculation of the HOMA1-IR. Both s-leptin and free s-adiponectin were analysed from frozen serum drawn at all sample times, both during OFTT and OGTT, using ELISA kits (DRG Diagnostics, Marburg, Germany) for s-leptin (sandwich ref. EIA-2395) and s-adiponectin (human, ref. EIA-4574), respectively. Leptin sensitivity was calculated as the ratio of Resting Energy Expenditure (REE) to fasting serum leptin. We performed REE measurements by a canopy test with an indirect calorimetry device from Medical Graphics CPX metabolic cart (St Paul, MN, USA). The test protocol is described by Larsen et al. Leptin to adiponectin ratio – A surrogate biomarker for early detection of metabolic disturbances in obesity. Nutrition, Metabolism and Cardiovascular Diseases. 2018. After the completion of REE measurement, the OGTT was performed. We used parametric tests on raw or transformed variables that resembled a normal distribution visually or by skewness/kurtosis. Otherwise, non-parametric tests were performed.